Modeling the optimal sequence of biologic therapies in plaque psoriasis in Spain. (1st January 2021) - Egeberg, Alexander; Danø, Anne; Pedersen, Mikkel H.; Sohrt, Anne; Borg, Emma; Notario, Jaime
Abstract: Aim: The purpose of this manuscript was to illustrate the impact of the place in the treatment sequence on the cost and cost-effectiveness of different biologics for patients with moderate-to-severe plaque psoriasis. Materials and methods: We developed a treatment sequence model and focused on seven different biological treatment options and 840 combinations of treatment sequences. The model converted cost of treatment to a cost per responder by dividing treatment cost by expected number of patients achieving PASI100 after 52 weeks of treatment. We used Spanish ex-factory price levels, dosing recommendations and real-world data on drug survival to calculate the treatment costs. Results: The most cost-effective treatment sequence was brodalumab–risankizumab–guselkumab–ixekizumab, with a cost per responder of €139, 281 during the first five years of treatment. In comparison, if brodalumab was not recommended as first-line therapy, total costs would increase by 7.4% to €149, 616. If brodalumab was not recommended as any of the first four lines of treatment, total costs would increase by 13.1% to €157, 527 relative to the most cost-effective treatment sequence. Conclusions: A sequential therapy model may improve efficiency in the treatment of psoriasis. According to our results, brodalumab as the first-line therapy in Spain leads to the most cost-effective treatment sequence.